Transesterification Of Palm Cooking Oil Using BiFeO3 Nanocatalyst - Razuki, Nor Amirah (2019)
A novel heterogeneous bismuth ferrite nanocatalyst was successfully synthesized via facile biotemplated technique (BiFeO3) using polysaccharides of kappa-carrageenan with an aim to study its efficiency transesterification reaction of palm cooking oil. Pure BiFeO3 with particle size of 95.8 nm was obtained using 1:2 molar ratio of Bi to Fe with 1 % carrageenan biotemplate and calcined at 823 K for 2 hours. The produced nanocatalyst possess high thermal stability and X-ray diffraction (XRD) result confirmed the purity of its rhombohedral crystalline phases.